The Influence of Teacher Emotion Management on Classroom Climate and Student Motivation in an Islamic School Setting - Andi Muhammad Adnan Rabbani; Astuti Darmiyanti (At-Takwin: Journal of Islamic Education Studies, 2025)
This study examines the urgency of teacher's emotional competence within the Islamic education context, which focuses not only on academic achievement but also on character building (akhlaqul karimah). The objective of this article is to theoretically and conceptually analyze the influence of teacher's emotion management on classroom climate and student learning motivation by integrating modern psychological frameworks with the principles of Islamic pedagogy. The research method employed is a systematic literature review with a thematic analysis of educational psychology journals, research within the Islamic education context, and scriptural evidence from the Qur'an and Hadith. The analysis reveals that a teacher's emotion management, explained through Goleman's Emotional Intelligence model and the Prosocial Classroom framework, significantly shapes a positive and supportive classroom climate. This climate, in turn, serves as a crucial mediator that enhances student learning motivation. In the Islamic educational context, the teacher's role as an Uswatun Hasanah (a good role model) reinforces this influence, while student learning motivation is deepened through the spiritual foundations of niyyah (intention) and the conceptualization of learning as a form of ibadah (worship). The implication of these findings is that emotional competence is not merely a professional skill but an integral part of the spiritual and pedagogical competencies that teachers in Islamic schools must possess to create a holistic learning environment